Cystic echinococcosis of the liver and lung treated by radiofrequency thermal ablation： An ex-vivo pilot experimental study in animal models - Lamonaca, Vincenzo; Virga, Antonino; Minervini, Marta Ida; Stefano, Roberta Di; Provenzani, Alessio; Tagliareni, Pietro; Fleres, Giovanna; Luca, Angelo; Vizzini, Giovanni; Palazzo, Ugo; Gridelli, Bruno (World journal of gastroenterology : WJG, 2009)
AIM： To evaluate radiofrequency thermal ablation （RTA） for treatment of cystic echinococcosis in animal models （explanted organs）. METHODS： Infected livers and lungs from slaughtered animals, 10 bovine and two ovine, were collected. Cysts were photographed, and their volume, cyst content, germinal layer adhesion status, wall calcification and presence of daughter or adjacent cysts were evaluated by ultrasound. Some cysts were treated with RTA at 150 W, 80℃, 7 min. Temperature was monitored inside and outside the cyst. A second needle was placed inside the cyst for pressure stabilization. After treatment, all cysts were sectioned and examined by histology. Cysts were defined as alive if a preserved germinal layer at histology was evident, and as successfully treated if the germinal layer was necrotic. RESULTS： The subjects of the study were 17 cysts （nine hepatic and eight pulmonary）, who were treated with RTA. Pathology showed 100% success rate in both hepatic （919） and lung cysts （8/8）; immediate volume reduction of at least 65%; layer of host tissue necrosis outside the cyst, with average extension of 0.64 cm for liver and 1.57 cm for lung; and endocyst attached to the pericystium both in hepatic and lung cysts with small and focal de novo endocyst detachment in just 3/9 hepatic cysts. CONCLUSION： RTA appears to be very effective in killing hydatid cysts of explanted liver and lung. Bile duct and bronchial wall necrosis, persistence of endocyst attached to pericystium, should help avoid or greatly decrease in v/vo post-treatment fistula occurrence and consequent overlapping complications that are common after surgery or percutaneous aspiration, injection and reaspiration. In vivo studies are required to confirm and validate this new therapeutic approach.